Necrotizing arteritis due to emerging Pythium insidiosum infection in patients with thalassemia: Rapid diagnosis with PCR and serological tests - Case reports - Kamphol Laohapensang (2018)
Pythium insidiosum is a pathogen that causes disease in both animals and humans. Human pythiosis is an emerging disease in the tropical, subtropical, and temperate regions of the world. Pythiosis occurs in localized and systemic or vascular forms. Most patients with arterial pythiosis have underlying hemoglobinopathy syndromes such as thalassemia, which exhibits a severe form. We present a series of eight cases of emerging human vascular pythiosis in northern Thailand and confirm that PCR and Immunoassay can make an early and accuracy diagnosis of vascular pythiosis. Prospective studies were made during a 38-month period from July 2001 to December 2004 of eight hemoglobinopathic patients with a distinct clinical syndrome characterized by progressive ischemia of the lower extremities, with ascending arteritis and aneurysm formation. One patient died when infection caused bifurcation of the aorta with arterial leakage before diagnosis and treatment. One patient refused any treatment and was lost to followup. All eight patients worked in wet and swampy areas (7 farmers and 1 horse stable worker). Pythium insidiosum was isolated from three patients and histopathologically diagnosed in five patients. Wet KOH preparation could identify nonseptate hyphae in only three patients. Rapid identification of Pythium insidiosum by immunoblot and PCR methods can provide diagnosis and management. There are no effective antimicrobial agents for this syndrome; radical surgical removal of infected tissue is the only way to ensure survival of the patient. Immunotherapy using P. insidiosum antigen (PIA) may be effective in treating human pythiosis. P. insidiosum infection should be considered in thalassemic patients with leg ulcer and arterial occlusion of the lower extremities.